2018
DOI: 10.1016/j.jcjd.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia and Prevalence of Depressive Symptoms in Japanese Adult Patients With Type 2 Diabetes Mellitus: The Dogo Study

Abstract: In Japanese female patients with type 2 diabetes, nocturia may be positively associated with depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We found that about 58% participants (N = 418) reported elevated depressive symptoms, which was similar to a study in Nanjing, China (51%) 6 and Saudi Arabia (53.8%), 9 but higher than the findings in the US (23.0%), 42 Germany (23.0%) 7 and Japan (16.8%) 8 among persons with T2DM at hospital settings. The variety of the proportion could be explained by the diabetes care practice gap across health-care systems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that about 58% participants (N = 418) reported elevated depressive symptoms, which was similar to a study in Nanjing, China (51%) 6 and Saudi Arabia (53.8%), 9 but higher than the findings in the US (23.0%), 42 Germany (23.0%) 7 and Japan (16.8%) 8 among persons with T2DM at hospital settings. The variety of the proportion could be explained by the diabetes care practice gap across health-care systems.…”
Section: Discussionsupporting
confidence: 87%
“…3 The worldwide prevalence of elevated depressive symptoms among persons with T2DM varies from 7.5% to 44.3%, 4,5 whereas it ranged from 16.8% to 53.8% among hospitalized patients due to the severity and complexity of disease. [6][7][8][9] The condition of depression or elevated depressive symptoms could worsen glycaemic control which in turn may exacerbate their depressive status. 10 The factors associated with depressive symptoms in persons with T2DM have received increasing attention in the literature and clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise habit was defined as positive if the study participants reported exercising 60 min or more per week during leisure time, regardless of the exercise intensity. The definitions of variables were previously described in detail. The definitions of microvascular diseases were based on the Classification of Diabetic Nephropathy 2014, the Fukuda standard and the abbreviated diagnosis of diabetic neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of nocturia was based on a questionnaire regarding the numbers of voids. We used the following outcomes: (i) nocturia was defined as ≥2 voids per night; and (ii) severe nocturia was defined as ≥3 voids per night.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation